(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Weeds are one of the most problematic, time-consuming, and expensive production issues for organic horticulturists. The need for novel bioherbicides to manage weeds has increased as organic agriculture has risen in importance. Pathogens, cosmetic compounds, and natural material extracts might all be made to produce bio herbicides. Two types of infectious pathogens that can be used as bio-herbicides are dangerous fungus and microbes. Herbicidal activity has been shown in by products of accepted birthplaces such as Dried-Distillers Grains with Soluble(DDGS), Corn-Gluten-Meal(CGM), and Mustard-Seed-Meals(MSMs). Bioherbicide potential has also been discovered in certain essential oil extracts. The effectiveness of a bio-herbicide is the primary restraining element in its application, and it may be influenced by variables like as humidity and moisture, application technique, bioherbicide spectrum, and formulation type. In addition to effectiveness, bioherbicide usage is limited by price and worries about possible human health risks. Because incorporating bio herbicide technology into current weed monitoring systems might well help manage resistance mechanisms, benefit from economies of scale, and increase crop yields, continued studies should concentrate on the improvement of more cost-effective and convenient bio-herbicides for pest management, as well as the efficiency of manufacturing techniques and traditional influences with the use of frontrunner bio-herbicides.